Ketotifen Treatment of Active Colitis in Patients with 5-Aminosalicylate Intolerance - John K Marshall; E Jan Irvine (Canadian Journal of Gastroenterology)
Mast cell stabilizers are commonly used in the treatment of asthma and allergic disorders. Although the role of mucosal mast cells in the pathogenesis of inflammatory bowel disease remains uncertain, mast cell stabilizers have been shown in animal models to attenuate the severity of experimental colitis. The authors' experience with ketotifen in three patients - one each with Crohn's disease, ulcerative colitis and collagenous colitis - who had demonstrated allergy to, or intolerance of, 5-aminosalicylic acid is reported.